De grote Vlaamse striproman. - Leyman, Dirk (Alsemberg : Hugo Bousset, 2021)
Herman, Gerard ; Conard, Sébastien ; Bassant, Patrick ; Conard, Sébastien ; Debroey, Shamisa ; Crucifix, Benoît ; Laudelout, Coralie ; Corre, Mélanie ; Pylyser, Charlotte ; Deprez, Olivier ; Comblain, Roby ; Baeken, Serge ; Conard, Sébastien ; Poot, Christophe ; Lens, Naninga ; Moerenhout, Peter ; van Driel, Guido ; Mertens, Sara ; Snoekx, Kurt ; Verschaffel, Martha ; La Cour, Erin ; Spanjers, Rik ; Sietiņa, Dace ; Baetens, Jan ; van Haren, Elma ; Meuleman, Bart ; Brassinga, Anneke ; Reumers, Melani ; van den Dool, Anne Louïse ; Hüsgen, Lucas ; vanden Broeck, Bob ; Thijs, Mona ; Temmerman, Max ; van Meenen, Vincent
boek